Defining smallholder agriculture in Ghana: Who are smallholders, what do they do and how are they linked with markets? - Chamberlin, Jordan (International Food Policy Research Institute, 2007)
Smallholders in Ghana, as elsewhere, are widely considered to be the largest as well as the most vulnerable component of the rural sector. Ghana professes national development objectives of reducing rural poverty through the increased productivity and commercialization of smallholder agriculture.... This work uses household survey data, district-level production data and a variety of mapped infrastructural and biophysical data to characterize the production environments and characteristics of smallholder agriculture. This paper explores the relevance of geographically-differentiated characteristics. Several key issues are highlighted: the less prevalent use of inputs, lower commercialization, and lower welfare rates of producers with smaller landholdings.